Utilization of Aur-Aur Grass as A Natural Hand Sanitizer in Order To Prevent The Spread of The Covid-19 Virus - Amutya, Adilla Lina Putri; Rifa'i, Alfian Zilham; Prasetiyo, Yogi; Sari, Arum; Saputri, Lestari Hetalesi (Indonesian Journal of Chemical Research, 2022)
Indonesia is currently amid a Covid-19 virus pandemic. One of the efforts that can be done to prevent the spread of the Covid-19 virus is to wash your hands with soap, or you can use a hand sanitizer. However, hand sanitizers are mostly made of chemicals, many people feel side effects including dry skin, dermatitis, and irritation. This research aims to make hand sanitizer products made from natural ingredients, namely from extracts of aur-aur grass (Commelina diffusa Burm F.). Phytochemical tests showed that aur-aur grass contained 5,188.73 ppm flavonoid compounds, 8,673.60 ppm total phenol (tannin), and 466.30 ppm alkaloids. The manufacture of hand sanitizers was carried out in four variations with each sample having aur-aur extract levels of 5%, 10%, 15%, and 20%. Of the existing hand sanitizer products, all of them have a pH of ±5 and get good responses from satisfaction values ​​above 80%. Hand sanitizer products also can inhibit bacterial growth. The increase in extract levels in the hand sanitizer is directly proportional to the ability to inhibit bacteria, as shown by sample D which has an average inhibition zone of 9.77 mm.